Pragmatic manifestation of high dynamic range imaging – A Review - Ahmad, Khursheed; Mittal, Sumit; Olanrewaju, Rashidah Funke (Thompson Reuters, 2016)
The real world images produce a range of brightness variations. However, the display systems used are able to operate on low dynamic range only i.e., they can reproduce only 8 bit data per pixel. This results in poor image quality as compared to what is visible to the human eye. Thus, in order to accommodate the vast dynamic range of natural scenes, a technique, referred to as High Dynamic Range Imaging(HDRI)has evolved in which the scenes having large intensity range can be captured unlike the traditional sensors. Therefore, HDRI is able to represent bright as well as dark portions in a scene faithfully. In this paper, the technology of high dynamic range imaging has been discussed. The various concepts in HDRI including the generation of high dynamic range image have been elucidated along with the storage formats used for HDR images. Further, various issues in obtaining quality high dynamic range images have also been conferred – like ghost artifacts and the effect on images due to motion of camera or objects. The paper also presents some of the future applications of the technology and is quite beneficial for researchers working in the domain of image processing, photography and computer graphics.